2011
DOI: 10.1097/jsm.0b013e31820758c7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Treatment for Ligament and Tendon Injuries

Abstract: Platelet-rich plasma (PRP) is derived from centrifuging whole blood, has a platelet concentration higher than that of the whole blood, is the cellular component of plasma that settles after centrifugation, and contains numerous growth factors. There is increasing interest in the sports medicine and athletic community about providing endogenous growth factors directly to the injury site, using autologous blood products such as PRP, to potentially facilitate healing and earlier return to sport after musculoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 45 publications
1
62
0
2
Order By: Relevance
“…Potential complications following the procedures are mild; therefore, this method of treatment appears to be safer in comparision with surgical techniques [4]. PRP injection applied by orthopaedic surgeons and sport medicine physicians to the knee, ankle, and elbow joints [11,12]. New studies suggest that PRP injection might be beneficial for TMJ ligament and cartilage healing [4].…”
Section: Discussionmentioning
confidence: 99%
“…Potential complications following the procedures are mild; therefore, this method of treatment appears to be safer in comparision with surgical techniques [4]. PRP injection applied by orthopaedic surgeons and sport medicine physicians to the knee, ankle, and elbow joints [11,12]. New studies suggest that PRP injection might be beneficial for TMJ ligament and cartilage healing [4].…”
Section: Discussionmentioning
confidence: 99%
“…6 Some studies have demonstrated that increased cellularity during early wound healing may have a positive impact on ligament and tendon; 7 however, other studies have found no such relationship. 8 This creates a problem in which physicians are unsure whether the treatment of PRP is justified.…”
Section: 5mentioning
confidence: 99%
“…1, 6 The actions of both of these growth factors can be seen with the improved work of fibroblasts on the treated group.…”
Section: Effect Of Insulin-like Growth Factor (Igf) As a Part Of Prpmentioning
confidence: 99%
“…3 On the other hand, autologous blood, PRP and autologous conditioned serum deliver growth factors to the diseased areas to stimulate the repair process. [4][5][6] Platelet-rich plasma (PRP) is defined as a sample of autologous blood with concentrations of platelets above baseline values. 26 Platelets play an instrumental role in the normal healing response via the local secretion of growth factors and recruitment of reparative cells.…”
Section: Introductionmentioning
confidence: 99%